Regionalism in the South Caucasus from a theoretical perspective : is the South Caucasus a region? - Abushov, Kavus (Eurasian Association of Scientists, 2011)
This article will attempt to shed light on the question of whether the South Caucasus is a region, and whether the nature of this regionalism is sufficiently established I to serve as the starting point of broader processes such as regional cooperation and integration. These questions will be answered with reference to the existing literature on regionalism. Notwithstanding the fact that the literature on regionalism is to some extent inconsistent and excessively abstract, the minimal and maximal criteria established are adequate to measure the regional dynamic of the South Caucasus. On their own, the minimal criteria are not sufficient to deepen regionalism to the extent of integration. Based on the application of existing theories on regionalism, the article concludes that the South Caucasus as a sub-region of the broader Caucasus has weak regional characteristics, which cannot provide the basis of any further integration. The components required for integration or a deeper level of regionalism are apparently absent in this region.
Caucasus International
Keywords: Caucasus -- Politics and government -- 21st century -- Periodicals.; Caucasus -- History -- Periodicals.